The cyclic-di-GMP signaling pathway in the Lyme disease spirochete, Borrelia burgdorferi - Novak, Elizabeth A.; Sultan, Syed Z.; Motaleb, Md. A. (Frontiers in Cellular and Infection Microbiology, 2014)
In nature, the Lyme disease spirochete Borrelia burgdorferi cycles between the unrelated environments of the Ixodes tick vector and mammalian host. In order to survive transmission between hosts, B. burgdorferi must be able to not only detect changes in its environment, but also rapidly and appropriately respond to these changes. One manner in which this obligate parasite regulates and adapts to its changing environment is through cyclic-di-GMP (c-di-GMP) signaling. c-di-GMP has been shown to be instrumental in orchestrating the adaptation of B. burgdorferi to the tick environment. B. burgdorferi possesses only one set of c-di-GMP-metabolizing genes (one diguanylate cyclase and two distinct phosphodiesterases) and one c-di-GMP-binding PilZ-domain protein designated as PlzA. While studies in the realm of c-di-GMP signaling in B. burgdorferi have exploded in the last few years, there are still many more questions than answers. Elucidation of the importance of c-di-GMP signaling to B. burgdorferi may lead to the identification of mechanisms that are critical for the survival of B. burgdorferi in the tick phase of the enzootic cycle as well as potentially delineate a role (if any) c-di-GMP may play in the transmission and virulence of B. burgdorferi during the enzootic cycle, thereby enabling the development of effective drugs for the prevention and/or treatment of Lyme disease.